IMPLEMENTASI APLIKASI PENERIMAAN SISWA BARU SMP IDN BOARDING SCHOOL - Mesra Betty Yel; Yuma Akbar; Frencis Matheos Sarimole; Candra Milad Ridha Eislam; Ikhwanul Kurnia Rahman; Miftahul Huda; Oky Tria Saputra7 (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
New Student Admission at each school is the most important because it is the entrance gate for prospective new students at the school and can obtain information about prospective new students through the student documents which of course must be archived for future needs. The system that runs on the New Student Admissions Information System At SMP IDN Boarding School are still many problems that are obtained, whether it's the student registration process, data archiving to reports to the Principal, there are many weaknesses, both from supporting data or the structure of the irregular input and selection process. , there are still many piles of data that have not been managed properly so that there can be duplication of data originating from the same process. The research method used for preparation of this community service report is a descriptive research method using the PHP programming language, while the techniques are interviews, observations, and literature studies. With this community service, it is hoped that can provide a solution in the form of a New Student Admission Application Program which can used for support and simplify the processing of the New Student Admission System.